An Attribute‐Based Signcryption Scheme and Its Application in Information Hiding. Issue 4 (1st July 2016) - Peng, Changgen; Wang, Weiru; Tian, Youliang; Yuan, Zhilong
Abstract : In order to provide a secure, reliable and flexible way to hide information, a new attribute‐based signcryption scheme based on ciphertext‐policy and its security proof are presented. This scheme not only can simultaneously fulfil both authentication and confidentiality in an efficient way, but also implements a hierarchical decryption in one group and also between different groups according to user's authority (different users satisfying the same access structure can be considered as a group). We provide a solution to information hiding using our proposed scheme which can embed ciphertext into a carrier. Because the hierarchical decryption property, different users will obtain different message from the same carrier. Illegal user can not get any information without private key because message existed in the carrier is ciphertext. Such solution can be applied in sharing important message under the public network.